Minsky and the Mainstream: Has Recent Research Rediscovered Financial Keynesianism? - Steven M. Fazzari (Levy Economics Institute of Bard College, 1999)
Hyman Minsky's research emphasized the central role of finance in modern economics at a time when finance was not important in most mainstream macroeconomic research. But in the 1980s, mainstream research began to explore the role of finance in firm and consumer behavior. This paper examines the extent to which this recent mainstream research captures Minsky's insights and whether it extends his work. I argue that recent work on micro foundations-the link between economic behavior and finance–complements Minsky's contributions and corresponding empirical research provides strong support for his argument that financial conditions affect expenditures. But large differences remain between Minsky and the mainstream paradigm, especially in the role played by the financial system in macroeconomic fluctuations. Furthermore, there is much in Minsky's Big Government–Big Bank policy framework that does not appear in recent mainstream work.
Keywords: 330